(untitled) (Orinoquia, 2020)
The general (GCA) and specific (SCA) combining ability and effects of five inbred lines of tropical endosperm maize from Sem Latam SA’s tropical maize breeding programme were estimated for obtaining theoretical information concerning the genetic effects governing yield components and to have more information available for selecting the best progenitors for developing and producing commercially interesting hybrids. Positive SCA effect values were found regarding specific combinatorial ability for yield-related characters; however, they were not significantly different from zero, resulting in the lack of a heterotic pattern concerning the lines evaluated here. Little capitalisation regarding such lines’ non-additive or dominant genetic effects concerning genealogical selection was seen here, thereby leading to interpreting the low manifestation of heterosis as an expression of the F1 crosses’ hybrid vigour compared to that of the parental genotypes.